SOME STUDIES ON ENERGY CONSUMPTIONS AND IDENTIFICATION OF SUITABLE ENERGY MANAGEMENT TECHNIQUES IN INDIAN FOUNDRY INDUSTRIES - Patange, Gajanan; Khond, Mohan (European Scientific Journal, ESJ, 2013)
﻿﻿The Indian foundry industry is the second largest in the world. There are more than 6,000 foundries in India. Most foundries (nearly 90%) in India fall under the small and medium scale category and are located in clusters. The foundry industry is energy intensive and has an important role to play from an environmental point of view whilst seeking to develop and play an important role in the nation’s continued economic development. In foundries energy accounting is necessary to determine where and how energy is being consumed and how efficient is the energy management system. There are many opportunities for improving energy efficiency in most foundries. Some of these, such as optimizing the efficiency of ancillary services can be achieved at minimal cost and make a valuable improvement to the bottom line. Reports from many foundries suggest that energy efficiency is one of the most significant cleaner production options still to be addressed in the industries. The study reveals that the two thirds of the energy consumed in a foundry is used for metal casting and holding operation. Considerable energy saving can be achieved by proper attention to this process with proper energy management. This paper presents a need of energy saving in Indian foundries. This gives an idea of the current energy consumption of the foundries, which can be compared with standard norms and can be used to implement in Indian foundries.